The complex set of internal repeats in SpTransformer protein sequences result in multiple but limited alternative alignments - Barela Hudgell, Megan A.; Smith, L. Courtney (Frontiers in Immunology, 2022)
SpTransformer (SpTrf) gene sequences have a series of internal repeats in a mosaic pattern that is characteristic of this family. This mosaic pattern necessitates the insertion of large gaps, which has made alignments of the deduced protein sequences computationally difficult such that only manual alignments have been reported previously. Because manual alignments are time consuming for evaluating newly available SpTrf sequences, computational approaches were evaluated for the sequences reported previously. Furthermore, because two different alignments of the SpTrf sequences are feasible because of the multiple internal repeats, it is not known whether additional alternative alignments can be identified using different approaches. The bioinformatic program, PRANK, was used as it was designed to align sequences with large gaps and indels. The results from PRANK shows that the alignments of the internal repeats are similar to those done manually, but that they were not as robust and optimal. GUIDANCE based analysis of the alignments identified regions that were excellent and other regions that failed to align for reasons that were unclear. This suggests that computational approaches have limits for aligning the SpTrf sequences that include multiple repeats and require inserted gaps. Furthermore, it is unlikely that alternative and optimal alignments of the SpTrf sequences will be identified.